Technological properties and probiotic potential of yeasts isolated from traditional low‐salt fermented Chinese fish Suan yu. Issue 8 (4th June 2019) - Zeng, Xuefeng; Fan, Jin; He, Laping; Duan, Zhenhua; Xia, Wenshui
Abstract: This study aims to investigate the technological properties of yeast strains isolated from traditional low‐salt fermented Suan yu fish as starter culture. A step‐by‐step approach was used to determine the technological properties of the isolated yeast strains. The enzymatic activity (catalase, urease, β‐glucosidase, protease, and lipase) under adverse conditions (pH, salt, and temperature) were evaluated. Principal component analysis was used to assess data. Twenty‐five strains with desirable technological properties were selected for evaluation of probiotic traits (tolerance at pH 2.5 and 0.3% bile salts, antimicrobial activity, hydrophobic properties, and biofilm production). These isolates were identified by sequencing the D1/D2 region of 26S rDNA. Finally, seven isolates with desirable probiotic traits were analyzed for their ability to survive through gastric transit using a gastrointestinal simulation model. An In vitro test showed that isolates 3, 12, 19, 24, and 43 exhibited high survival levels (60%–70%), similar to those of the indicator strain ( Saccharomyces cerevisiae ). The results suggest that five isolates ( S. cerevisiae strains 3, 12, 19, 24, and 43) showed desirable technological properties and probiotic traits and therefore can be used as functional starter cultures to produce fermented fish products. Practical applications: Researchers have investigated the activity of LAB as functional and probiotic microorganisms; however, information on the probiotic potential of yeasts remains limited. Yeasts are microorganisms that present and induce biochemical changes in several fermented meat and fish products. In the present study, the technological and probiotic properties of 52 isolates from Suan yu were investigated to identify potential probiotic strains for starter cultures. Our results suggest that five isolated S. cerevisiae strains showed desirable technological properties and probiotic traits and therefore can be used as functional starter cultures to produce fermented fish products, and other fermented foods. Functional yeast isolates are used to effectively improve the quality of fermented fish products for consumer acceptance. This study has focused on the possibility to produce a functional Suan yu using a potential probiotic S. cerevisiae as starter culture to enhance health benefits. Abstract : The PCA plot explained 48.1% of the total variance, which indicated several technological properties of the isolates from Suan yu. Subgroup B1 included strains 3, 12, 24, and 43, which exerted strong proteolytic, lipolytic, catalase, and β‐glucosidase activity, and strong survival ability under severe acidity, temperature, and NaCl concentration.